2014 IEEE International Ultrasonics Symposium 2014
DOI: 10.1109/ultsym.2014.0217
|View full text |Cite
|
Sign up to set email alerts
|

CTGS material parameters obtained by versatile SAW measurements

Abstract: Recently big size high quality piezoelectric single crystals of Ca3TaGa3Si2O14 (CTGS) have been grown. This temperature durable crystal is very promising for future application in different devices based on surface acoustic waves (SAW) due to its high electromechanical coupling compared to quartz. In contrast to the popular langasite, CTGS is a more ordered compound and therefore stands for better characteristics at both, high temperatures and high frequencies. During the last decade several sets of material c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…This observation demonstrated that the above constants do not change linearly with increasing of Al content in the Al-doped CTGS. However, the constants of CTGS reported in [2] were significantly different from those obtained in [13], and the maximum difference of 55% was observed for the elastic constants. Based on our experience [10], this mismatch is associated with measurement method utilised in [2], but not with different crystal quality.…”
contrasting
confidence: 62%
“…This observation demonstrated that the above constants do not change linearly with increasing of Al content in the Al-doped CTGS. However, the constants of CTGS reported in [2] were significantly different from those obtained in [13], and the maximum difference of 55% was observed for the elastic constants. Based on our experience [10], this mismatch is associated with measurement method utilised in [2], but not with different crystal quality.…”
contrasting
confidence: 62%
“…There are many reports on determination of the material constants. [18][19][20][21] In previous works, we have measured the Al content dependence of acoustic properties of CTGAS(x) using the ultrasonic microspectroscopy (UMS) technology, [22][23][24] which showed a linear relationship between acoustic properties and Al content. 25) However, the temperature dependence of acoustic properties has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…This material has better piezoelectric properties, such as higher effective piezoelectric coefficient at high temperature. The crystals have better quality due to the lower Ga content, higher electrical resistivity, higher mechanical strength and a lower thermal expansion anisotropy as compared to langasite [20,21,22,23]. This relatively newer substrate material is lesser known and thin films on it are not extensively studied yet.…”
Section: Introductionmentioning
confidence: 99%